The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1101/gad.290379.116
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic α- and β-cellular clocks have distinct molecular properties and impact on islet hormone secretion and gene expression

Abstract: A critical role of circadian oscillators in orchestrating insulin secretion and islet gene transcription has been demonstrated recently. However, these studies focused on whole islets and did not explore the interplay between α-cell and β-cell clocks. We performed a parallel analysis of the molecular properties of α-cell and β-cell oscillators using a mouse model expressing three reporter genes: one labeling α cells, one specific for β cells, and a third monitoring circadian gene expression. Thus, phase entrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
139
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 90 publications
(155 citation statements)
references
References 60 publications
15
139
0
Order By: Relevance
“…Indeed, these oscillators are not coupled even when cells are establishing tight physical contacts in confluent cell culture, as was demonstrated by co‐culture experiments between fibroblast cells bearing distinct oscillatory characteristics . In line with the reported cell‐autonomous nature of the peripheral oscillators, pronounced circadian oscillations were registered not only in isolated intact rodent and human pancreatic islets, but also in dispersed islet cells cultured in monolayer . These findings imply that physical interactions between neighbouring cells within the 3‐dimensional islet architecture may be dispensable for cellular oscillator function.…”
Section: Molecular Characterization Of Pancreatic Islet Circadian Clockssupporting
confidence: 54%
See 3 more Smart Citations
“…Indeed, these oscillators are not coupled even when cells are establishing tight physical contacts in confluent cell culture, as was demonstrated by co‐culture experiments between fibroblast cells bearing distinct oscillatory characteristics . In line with the reported cell‐autonomous nature of the peripheral oscillators, pronounced circadian oscillations were registered not only in isolated intact rodent and human pancreatic islets, but also in dispersed islet cells cultured in monolayer . These findings imply that physical interactions between neighbouring cells within the 3‐dimensional islet architecture may be dispensable for cellular oscillator function.…”
Section: Molecular Characterization Of Pancreatic Islet Circadian Clockssupporting
confidence: 54%
“…Peripheral oscillators operative in liver, skeletal muscle, adipose tissue, thyroid gland, endocrine pancreas and other organs orchestrate physiological functions within these organs, adjusting them on a daily basis to the rest‐activity and feeding‐fasting cycles of the body . Genome‐wide transcriptome profiling studies of peripheral oscillators indicate that the temporal orchestration of metabolism and xenobiotic detoxification is a major purpose of circadian clocks in peripheral tissues . It was recently suggested that in mouse liver circadian gene expression is controlled by rhythmic chromatin interactions between enhancers and promoters.…”
Section: Body Metabolism Is Orchestrated By Circadian Clocks In Rodenmentioning
confidence: 99%
See 2 more Smart Citations
“…31,54,61,[65][66][67][68][69][70][71][72][73][74][75][76][77] Interestingly, circadian phases of the core clock components, as well as of a high number of key functional genes, were not aligned between α-and β-cells within the pancreatic islet, which may play a role in fine-tuning of temporal profiles of insulin and glucagon secretion. [61][62][63][64] In agreement with rodent studies, emerging work in humans conducted through serial tissue biopsies collected across 24 hours, and in primary cells synchronized in vitro, suggest that a considerable portion of transcripts in these organs exhibit rhythmic expression. 31,41,[78][79][80] Circadian transcription reconstruction analysis through cyclic ordering by periodic structure (CYCLOPS) conducted by John Hogenesch and colleagues across 13 tissues derived from a cohort of over 600 human donors provides a valuable database for future studies of clock outputs in humans.…”
Section: Of Mammalian Physiology and Metabolismmentioning
confidence: 99%